Literature Review : Pengaruh Pendidikan Kesehatan Tentang Respon Fisik Pada Menstruasi Terhadap Pengetahuan Remaja Putri - Tumurang, Marjes Netro; Killing, Maykel; Bobaya, Janbonsel; Karundeng, Yani; Kawatu, Yosua; Tuegeh, Johana; Keintjem, Femmy; Runtu, Lorrien G. (POLTEKKES KEMENKES MANADO, 2023)
Background : The physical response during menstruation is a natural process that occurs in young women who have experienced menstruation, therefore it is very important for young women to receive health education about menstruation so as to increase their knowledge and understanding of changes in physical changes during menstruation. Objective: This study was to determine the effect of health education on physical responses to menstruation on the knowledge of young women. Method : This study uses the type of research literature review, namely a study that uses the results of research that has been carried out by previous researchers, in the form of research journals, or books, to obtain accurate data according to the topic of discussion, the author conducts a search literature based nationally and internationally using four databases via Pubmed, Science direct, Google Scholar, andFeel by using the keywords health education, physical response, menstruation, knowledge of adolescents, young women, level of education. Conclusion : namely there is an influence of health education about the physical response to menstruation on the knowledge of young women.